2015
DOI: 10.1093/femsec/fiv052
|View full text |Cite
|
Sign up to set email alerts
|

Environmental drivers of the distribution of nitrogen functional genes at a watershed scale

Abstract: To date only few studies have dealt with the biogeography of microbial communities at large spatial scales, despite the importance of such information to understand and simulate ecosystem functioning. Herein, we describe the biogeographic patterns of microorganisms involved in nitrogen (N)-cycling (diazotrophs, ammonia oxidizers, denitrifiers) as well as the environmental factors shaping these patterns across the Koiliaris Critical Zone Observatory, a typical Mediterranean watershed. Our findings revealed that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
21
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 53 publications
3
21
3
Order By: Relevance
“…Thereby, we may expect that pH had little impact on the AOA responses to N additions in the current study. In addition, changes in soil moisture may influence nitrification‐related microbial growth (Tsiknia et al, ). It has been reported that N addition might cause soil water depletion owing to increased plant growth and leaf transpiration (Xia et al, ; Zhang et al, ) and decreased soil water content might constrain microbial growth.…”
Section: Discussionmentioning
confidence: 99%
“…Thereby, we may expect that pH had little impact on the AOA responses to N additions in the current study. In addition, changes in soil moisture may influence nitrification‐related microbial growth (Tsiknia et al, ). It has been reported that N addition might cause soil water depletion owing to increased plant growth and leaf transpiration (Xia et al, ; Zhang et al, ) and decreased soil water content might constrain microbial growth.…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesized that the taxa responsible for each pathway would vary greatly by habitat type, because the habitat would select for specialized taxa. We further predicted that soil pH-previously identified as an important driver of soil composition (25,26)-would also influence compositional variation within microorganisms encoding N-cycling traits.…”
mentioning
confidence: 93%
“…Most authors have studied soil grassland bacterial diversity on a single or a few mountain transects, notably to emphasize the elevation factor in mountain ecosystems (3)(4)(5)(6)(7)(8). However, alpine studies that span an important horizontal surface area, along with the vertical elevation gradient, are much fewer, despite that mountain ecosystems are composed of a large spectrum of different topographic, climatic, soil physical, and chemical conditions, interspersed with a wide range of microclimates occupied by varied vegetation and animal populations (2,(9)(10)(11)(12).…”
mentioning
confidence: 99%